Peran Keluarga Terhadap Perilaku Pembelian Kompulsif Remaja - Andriyanto, Sonny (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
Compulsive buying is a psychosocial symptom as indicated by excessive buying behavior, even items purchased not always have a positive use value. This study analyzes the existing compulsive buying in adolescence and review of the role offamily factors. The hypothesis is there a relationship between compulsive buying behavior in families with several factors, including a divorce in the family, the family members of deviant behavior, patterns' communication in families, parental yielding, and the perceptions of parents of compulsive buying. The subject of this research is student of senior high school and university in Yogyakarta. This research using compulsive buying scale, deviant behavior of family member scale, pattern communication in families scale, parental yielding scale, and perceptions of parents of compulsive buying scale.Through a quantitative approach to the studyfound that of the severalfactors mentioned, there is only perception of compulsive buying factor that has a positive influence on compulsive buying behavior. Regression analysis showed that compulsive buying behavior in adolescents, 8.2 % is determined by the perception of the parents and the rest of the behavior is influenced by otherfactors. The more positive perception ofthe parents, then the compulsive buying behavior in which appears also higher. Conversely, the more negative the perception of older people who appear compulsive buying is also lower.Key words: Compulsive buying, family factors